Knowledge Brief : When, Why, and How Water and Sanitation Utilities Can Benefit from Working Together - World Bank Group (World Bank, Washington, DC, 2017)
The World Bank Water Global Practice, under the WSS GSG Utility Turnaround thematic area, has implemented the Global Study on WSS Utility Aggregation to provide evidence-based guidance to policy makers and practitioners regarding when, why, and how water and sanitation utilities can work together, or aggregate, to successfully deliver specific policy outcomes, such as better services or lower costs. Aggregation has been regarded as an opportunity to improve cost efficiency and performance of service delivery through economies-of-scale and cost-sharing, as well as enhanced human capacity. However, the study shows that successful aggregation—where the aggregated service provider performs significantly better than the previously disaggregated entities regarding the intended purpose, without unreasonable deterioration of other performance dimensions—is not always guaranteed. This work presents and reviews global evidence, analyzes specific aggregation case studies, and identifies the key characteristics that successful aggregations have in common, depending on their purpose and the context in which they occur. This knowledge brief summarizes the study outcomes, which are detailed further in the main report, Joining Forces for Better Services? When, Why, and How Water and Sanitation Utilities Can Benefit from Working Together. The accompanying toolkit (accessible at www.worldbank.org/water/aggregationtoolkit), offers a broader set of resources to inform aggregation processes.